2014
DOI: 10.2147/ijgm.s61297
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of celecoxib and naproxen versus placebo in Hispanic patients with knee osteoarthritis

Abstract: BackgroundCelecoxib is an effective treatment for osteoarthritis (OA). However, information on its efficacy and safety profile in different racial/ethnic groups is limited. Noticeable differences among racial groups are found in other disease states, but a thorough investigation of OA is lacking. The objective of this study was to determine if celecoxib 200 mg once daily is as effective as naproxen 500 mg twice daily in the treatment of OA of the knee in Hispanic patients.MethodsHispanic patients aged ≥45 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…However, it must be noted that the LSM change in arthritis pain (VAS) score was also high in the placebo group (−33.6 mm) compared with celecoxib (−37.1 mm) and naproxen (−37.5 mm) treatment. A similar finding was noted in the study of these treatments when carried out in Africa American patients12 and, to a lesser degree, Hispanic patients 13. A previous meta‐analysis has reported that the placebo effect in OA studies is high, and can be influenced by a number of factors, including sample size and baseline disease severity 22.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…However, it must be noted that the LSM change in arthritis pain (VAS) score was also high in the placebo group (−33.6 mm) compared with celecoxib (−37.1 mm) and naproxen (−37.5 mm) treatment. A similar finding was noted in the study of these treatments when carried out in Africa American patients12 and, to a lesser degree, Hispanic patients 13. A previous meta‐analysis has reported that the placebo effect in OA studies is high, and can be influenced by a number of factors, including sample size and baseline disease severity 22.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, similar improvements from baseline to week 6 in the Patient's Assessment of Arthritis Pain VAS were noted for the active treatment groups in Asian patients, when compared to the studies carried out in patients of different ethnicities 12, 13…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations